Zniszczenie Wiślicy w 1135 roku w świetle przekazów źródłowych i literatury historycznej (część I: źródła) = Destruction of Wiślica in 1135 in light of source records and historical literature (part 1: sources) - Benyskiewicz, Krzysztof (1959- ) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article entitled "Destruction of Wiślica in 1135 in light of source records and historical literature (part 1. Sources)" is the first part of a two-part cycle dedicated to the presentation of source records and historical research related to the invasion of the city in 1135. The author analyses messages from medieval chronicles and annals, and records the results of archaeological research conducted in the area of Wiślica over several decades.
Keywords: Kadłubek, Wincenty (1150-1223); Rościsławic, Wołodar ( -1124); Włostowic, Piotr (1080-1153); Wiślica; roczniki polskie; Polish annals